Brain gym affect stress levels in narcotics inmates - Faza, Indiana Putri Wijaya; Mamnuah (International Journal of Health Science and Technology, 2024)
Inmates experience stress due to inner tension that arises as a result of incompatibility in the prison environment, so a way is needed so that stress can be overcome, one way to overcome stress is by brain gym. The purpose of this study is to determine the effect of brain gym on stress levels in narcotics inmates in Narcotics Prisons. This study uses a quasi-experimental research design in the form of a pretest-posttest design with control group. The research instrument used a questionnaire. The subjects in this study are narcotics inmates, as many as 26 people in the experimental group and 26 people in the control group. The data analysis technique used is a non-parametric static technique, a paired sample t-test with a significant level of 5%. The results of the t-stress test in narcotics inmates in the control group obtained a t-count value of (1.581) < t table (2.059) and a p-value (0.127) > 0.05, the results in the experimental group obtained a t-count value of (3.586) < t-table (2.059) and a p-value (0.001) < 0.05. There was an effect of brain gymon the experimental group. The results of the unpaired sample t-test obtained a result of 0.000, meaning there was a difference in stress levels in the experimental and control groups. Brain gym affect reducing stress levels in prisoners. Advice for drug addict inmates to apply brain gym independently to reduce stress levels in themselves.